1992
DOI: 10.1111/j.1432-1033.1992.tb17448.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a pore‐forming protein from the marine sponge Tethya lyncurium

Abstract: A pore-forming protein was detected and purified for the first time from a marine sponge (Tethyu lyncurium). The purified protein has a polypeptide molecular mass of 21 kDa and a pf of 6.4. Tethyu pore-forming protein (also called Tethya hemolysin) rapidly lysed erythrocytes from a variety of organisms. After binding to target membranes, the hemolysin resisted elution with EDTA, salt or solutions of low ionic strength and hence resembled an integral membrane protein. Erythrocytes could be protected from hemoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 59 publications
2
16
0
1
Order By: Relevance
“…Também não foi encontrado na literatura referência de atividade hemolítica devido a lectinas em extratos de esponjas marinhas. No entanto, além da proteína tóxica suberitina, foram descritos como responsáveis pela atividade hemolítica em extratos de esponjas polímeros de alquilpiridinas e outros compostos não identifi cados (Berlinck et al, 1996;Bourget et al, 1988;Cariello;Zanetti, 1979;Mangel et al, 1992;Sepcic et al, 1997).…”
Section: Resultsunclassified
“…Também não foi encontrado na literatura referência de atividade hemolítica devido a lectinas em extratos de esponjas marinhas. No entanto, além da proteína tóxica suberitina, foram descritos como responsáveis pela atividade hemolítica em extratos de esponjas polímeros de alquilpiridinas e outros compostos não identifi cados (Berlinck et al, 1996;Bourget et al, 1988;Cariello;Zanetti, 1979;Mangel et al, 1992;Sepcic et al, 1997).…”
Section: Resultsunclassified
“…Furthermore, studies with drugs have shown that agonists of TLRs can initiate the release of perforin in human CD8 ϩ cells (24). From earlier studies, it is known that also in sponges, perforin-related molecules exist; from the sponge Tethya lyncurium, a pore-forming protein had been isolated (55), and recently a first cDNA encoding a perforin-like protein was isolated (47).…”
Section: Discussionmentioning
confidence: 99%
“…Well-known members of these proteins are the poreforming cytolysins such as the alpha-toxin from S. aureus (14), streptolysin O (35), E. coli hemolysin (3), hemolysin from Tethya lyncurium (29), and Leishmania cytolysin (32). The mechanism of membrane damage by the pore-forming proteins involves the binding of the toxin to the target cell membrane and penetration followed by disruption of the membrane and alteration of membrane permeability, leading to cytolysis (37).…”
Section: Discussionmentioning
confidence: 99%